IMPROVING FINANCIAL LITERACY THROUGH TEACHING MATERIALS ON MANAGING FINANCE FOR MILLENNIALS - Markus Asta Patma Nugraha; Vivid Violin; Samuel PD Anantadjaya; Nurlia Nurlia; Arkam Lahiya (SEAN Institute, 2023)
Financial literacy is essential for the younger generation since it enables them to effectively manage their resources and attain their long-term financial objectives. Therefore, young people should acquire financial management knowledge and incorporate it into their daily life. Therefore, the project intends to equip the millennial age with an awareness of financial literacy through website-based digital teaching materials that can be easily accessed online by the younger generation. Quantitative techniques, such as questionnaires, are used to collect data on the financial literacy of young respondents, particularly college students. The results of the study are freely accessible digital teaching materials on financial literacy, the content of which consists of 15 digital book page views; each material is tailored to the needs of respondents in terms of understanding financial literacy and the benefits of financial management management and planning savings and investment knowledge